Let’s solve each problem step by step.
-
Finding the length of the diagonal of a square: If the side of the square is \(s\), then by the Pythagorean theorem, the diagonal \(d\) can be calculated as: \[ d = \sqrt{s^2 + s^2} = \sqrt{2s^2} = s\sqrt{2} \] Without specific information given about \(s\), I cannot provide a numeric answer.
-
Finding the length between the points (2, 5) and (7, 3): Use the distance formula: \[ d = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \] where \((x_1, y_1) = (2, 5)\) and \((x_2, y_2) = (7, 3)\). \[ d = \sqrt{(7 - 2)^2 + (3 - 5)^2} = \sqrt{5^2 + (-2)^2} = \sqrt{25 + 4} = \sqrt{29} \approx 5.39 \] So the answer is 5.39.
-
Finding the length between the points (-1, 6) and (5, -2): Using the distance formula again: \[ d = \sqrt{(5 - (-1))^2 + (-2 - 6)^2} = \sqrt{(5 + 1)^2 + (-8)^2} = \sqrt{6^2 + (-8)^2} = \sqrt{36 + 64} = \sqrt{100} = 10 \] So the answer is 10.
-
Finding the length between the points (-2, -1) and (2, 4): Again, use the distance formula: \[ d = \sqrt{(2 - (-2))^2 + (4 - (-1))^2} = \sqrt{(2 + 2)^2 + (4 + 1)^2} = \sqrt{4^2 + 5^2} = \sqrt{16 + 25} = \sqrt{41} \approx 6.40 \] So the answer is 6.40.
-
Finding the length between the points (2, -3) and (5, 5): Finally, apply the distance formula: \[ d = \sqrt{(5 - 2)^2 + (5 - (-3))^2} = \sqrt{(3)^2 + (5 + 3)^2} = \sqrt{3^2 + 8^2} = \sqrt{9 + 64} = \sqrt{73} \approx 8.54 \] So the answer is 8.54.
In summary:
- Diagonal of the square: Not enough information provided.
- Distance between (2, 5) and (7, 3): 5.39
- Distance between (-1, 6) and (5, -2): 10
- Distance between (-2, -1) and (2, 4): 6.40
- Distance between (2, -3) and (5, 5): 8.54